A novel gene therapy for methamphetamine- induced cognitive disorder with a hyper-acidified fusion variant of DnaJB1 - Mengru Zhang; Cheng Chen; Qingyan Peng; Xiaocong Wu; Ruiyi Zhou; Yuru Ma; Zhurong Zou (Elsevier, 2023)
Methamphetamine (MA) is spread worldwide and is a highly addictive psychostimulant that can induce neurodegeneration and cognitive disorder, which lacks effective treatments. We and other researchers have found that the crucial member of Hsp70 chaperone machinery, DnaJ, is liable to be co-aggregated with aberrant proteins, which has been confirmed a risk factor to promote neurodegeneration. In the current study, we demonstrated that tailing with a hyper-acidic fusion partner, tua2, human DnaJB1 could resist the formation of toxic mutant Tau aggregates both in prokaryote and eukaryote models. We found that aberrant Tau aggregates could deplete the antioxidant enzyme pool and disturb Hsp70 molecular chaperone system by co-aggregating with the principal members of these systems. Stability-enhanced DnaJB1-tua2 could stop the chain reaction of Tau aggregates as well as maintain redox balance and protein homeostasis. With an MA-induced cognitive disorder mouse model, we found that the cognitive disorder of MA mice was rescued and the overactivated inflammatory response was relieved by the expression of DnaJB1-tua2 in the hippocampus. Furthermore, the Tau neurofibrillary tangles and apoptotic neurons were diminished with the escorting of DnaJB1-tua2. These findings demonstrate that delivering DnaJB1-tua2 in hippocampus may have a therapeutic potential in the treatment of MA-induced cognitive disorder.